Design of Multiband Antenna for Wimax and WLAN Applications Using DGS - R, Banuprakash; Amith, GSPN; N, Gagana; AG, Ravi; C, Pavanashree (International Journal of Engineering and Technology, 2018)
In this paper, a multiband antenna with a micro strip feed line is presented. This antenna is designed on FR4 substrate with dielectric constant 4.4 having overall size of 20 Ã— 20 Ã— 1.6mm3. The proposed antenna comprises defected ground structure with T and L shape slots to achieve multiband frequencies. This multiband antenna covers three different frequencies as 3.3 GHz, 3.85 GHz and 5.25 GHz. All of these frequencies are applicable for WiMAX and WLAN applications respectively. Return loss (S11), Gain and Radiation patterns are simulated and observed on HFSS.Â Â